Role of Vesicular Monoamine Transporter2 (VMAT2) Inhibitors in Hyperkinetic Movement Disorders - A Brief Review - Nikkhah, Ali (Iranian Journal of Child Neurology, 2021)
Hyperkinetic movement disorders are a common group of movement abnormalities in children that defined as repetitive unintended involuntary movements. Major hyperkinetic movements contain tremor, tic, dystonia, myoclonus and chorea. Although, there are frequent drugs that effective on these abnormalities, but some of these are resistant to conventional treatments. Vesicular monoamine transporter2 (VMAT2) inhibitors (Tetrabenazine, Deutetrabenazine and Valbenazine) are new agents that have been introduced in the last decade for treatment some movement disorders in particular tardive dyskinesia, Huntington chorea and Tourette syndrome. In this brief review, we reviewed the role of these drugs on hyperkinetic movement disorders.